Co-activation of cultured human natural killer cells: enhanced function and decreased inhibition - Urlaub, Doris; Bhat, Rauf Ahmed; Messmer, Birgitta; Watzl, Carsten (Journal of toxicology and environmental health. Part A, 2016)
Natural killer (NK) cells are important immune effector cells that protect the organism against viral infections and cancer. The cytotoxic activity of NK cells is induced by the engagement of a number of different activating surface receptors and controlled by inhibitory receptors to ensure self-tolerance. Resting NK cells need to be co-activated by involvement of at least two distinct activating receptors in order to induce their functional activity. However, in cultured NK cells, which have been expanded in cytokines such as interleukin (IL)-2, the engagement of a single activating receptor may be sufficient to induce their function. Data demonstrated that also cultured NK cells may be co-activated by involvement of certain combinations of activating receptors. This co-activation results in enhanced activation of Vav-1 and ERK signaling pathways and produces greater degranulation. In addition to enhanced functionality, co-activation makes NK cells more resistant to the effect of inhibitory receptors, thereby inducing more potent and efficient NK cell responses.
Gesehen am 29.05.2020